Training management and teaching staff educational institutions of Ukraine in the first years of independence to present (Pedagogy of Higher and Secondary Education, 2013)
Bilanyn G. І. Training management and teaching staff educational institutions of Ukraine in the first years of independence to present.The article examines the state of the organization of training courses of management and teaching staff of educational institutions in the early years of independence, in the context of globalization and integration (1991-present). The forms, contents, duration and frequency of training courses of management and teaching staff in the period of research are revealed.
Keywords: training courses; management and teaching staff; program courses form and content; program courses; form and content